Mental health and use of Medicare Benefits Schedule follow-up mental health services by Indigenous people in Australia during the COVID-19 pandemic - Usher, Kim; Jackson, Debra; Peng, Wenbo; Amarasena, Suruchi; McCowan, Debbie; Miller, Joe; Cashman, Belinda; Sibbritt, David (Frontiers in Public Health, 2023)
Background: Mental health care has declined during the COVID-19 pandemic as has attendance for preventive mental health health services. This study aimed to investigate trends in all types of mental health service claims identified in an Indigenous-specific health assessment for Indigenous people before and during COVID-19. Methods: We conducted an analysis of Medicare Benefits Scheme (MBS) mental health service items (Items 81325 and 81355), to investigate the trends in all types of mental health service claims specifically intended for Indigenous people of Australia. Data were analysed using descriptive statistics, including the total annual numbers of Indigenous peoples' mental health service claims crosstabulated by age groups and gender, between the calendar years 2017-2021. Multivariable Poisson regression modelling was used to determine associations that were statistically significant. Results: Our results indicate an overall rise in MBS claims for mental health follow-up services during 2019-2020 followed by a decline in 2020-2021. In addition, there was an overall decline in claims for follow-up psychology services across the time period 2019-2021. Conclusion: We found a significant decline in MBS items specific to follow-up mental health services (MBS Items 81325 and 81355) for Indigenous people in Australia suggesting a decline in attendance for mental health service follow-up which in turn may indicate a deficit in mental health care during the COVID-19 pandemic, an issue that may lead to poorer mental health outcomes in the future. Further research is needed to understand whether these changes were due to the impact of the COVID-19 pandemic or other factors.